Maternal Mortality Risk Factors Based On An Epidemiological Approach - Yermi Yermi; Jois Nari; Masrikat Maya Diana Claartje (International Journal of Health Sciences, 2026)
Maternal mortality remains a serious public health problem, especially in developing countries. The Maternal Mortality Rate (MMR) is an important indicator in assessing the level of public health and the quality of maternal health services. An epidemiological approach is used to identify risk factors contributing to maternal mortality through an analysis of people, place, and time. This article aims to examine the risk factors for maternal mortality based on an epidemiological approach. The method used is a literature review of epidemiology textbooks, national health reports, and scientific journals. The results of the study indicate that risk factors for maternal mortality include biological, behavioral, socioeconomic, access to health services, and health care system factors. It is concluded that preventing maternal mortality requires a comprehensive and cross-sectoral approach.